2010
DOI: 10.1093/jnci/djq072
|View full text |Cite
|
Sign up to set email alerts
|

Fruit and Vegetable Intake and Overall Cancer Risk in the European Prospective Investigation Into Cancer and Nutrition (EPIC)

Abstract: A very small inverse association between intake of total fruits and vegetables and cancer risk was observed in this study. Given the small magnitude of the observed associations, caution should be applied in their interpretation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
234
0
14

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 367 publications
(252 citation statements)
references
References 27 publications
4
234
0
14
Order By: Relevance
“…Are (38)(39)(40)(41) . Consumption of fruit and vegetables has consistently been inversely associated with risk of CVD, and this has been confirmed by meta-analyses (42)(43)(44) .…”
Section: Type 2 Diabetes Mellitusmentioning
confidence: 99%
“…Are (38)(39)(40)(41) . Consumption of fruit and vegetables has consistently been inversely associated with risk of CVD, and this has been confirmed by meta-analyses (42)(43)(44) .…”
Section: Type 2 Diabetes Mellitusmentioning
confidence: 99%
“…An increasing number of studies indicate that increased consumption of fruits and vegetables can reduce the risk of chronic degenerative diseases such as cardiovascular disease, cancers, and others (Boffetta et al, 2010;Gandini, Merzenich, Robertson, & Boyle, 2000;van Duijnhoven et al, 2009). The associated beneficial effects have been attributed to various components but in general to those that, in vitro at least, act as antioxidants including phenolics, ascorbic acid, carotenoids and tocopherols (Ames, Shigenaga, & Hagen, 1993;Halliwell, 1996;Huxley & Neil, 2003;Knekt et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Dr. Boffetta referred to his article on fruit and vegetable intake in relation to cancer risk (7). In this prospective analysis of the European Prospective Investigation into Cancer and Nutrition cohort, he and his colleagues showed that associations between reduced cancer risk and increased intake of total fruits and vegetables combined and total vegetables for the entire cohort were similar [200 g/d increased intake of fruits and vegetables combined, HR ¼ 0.97, 95% confidence interval (CI) ¼ 0.96-0.99; 100 g/d increased intake of total vegetables, HR ¼ 0.98, 95% CI ¼ 0.97-0.99]; intake of fruits showed a weaker inverse association (100 g/d increased intake of total fruits, HR ¼ 0.99, 95% CI ¼ 0.98-1.00).…”
Section: Introductionmentioning
confidence: 99%